Association of Aquatic Plants and Fish in Lake Bokuok, Aursati Village, Tambang Subdistrict, Kampar Regency, Riau - Afael, Rizky Fauzi; Eddiwan, Eddiwan; Mulyani, Isma (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Lake Bokuok is an oxbow lake located in Aursati Village, Tambang District, Kampar Regency, Riau Province. This lake has undergone changes due to human activities, affecting the existence of aquatic organisms, including plants and fish. This study aims to determine the relationship between aquatic plants and fish in Lake Bokuok. Data collection was carried out in February-March 2025 using a survey method. Aquatic plant samples were collected once for species identification and four times for density calculations, while fish samples were collected four times for fish count calculations. The study results showed differences in aquatic plant density and total fish numbers across the three stations. Among the three stations, four aquatic plant species and four fish species were identified. Station III had the highest aquatic plant density and relative density (57.32 Ind/m²), which also correlated with the highest fish count (59 individuals). Conversely, Station II had the lowest aquatic plant density (25.08 Ind/m²) and the fewest fish (33 individuals). Statistical analysis showed a positive correlation between aquatic plant density and fish abundance, though the relationship was not statistically significant. Water quality in the lake is still considered suitable for supporting aquatic organisms. This study provides an initial overview of the role of aquatic plants in supporting fish life in natural lakes. These results are significant as a basis for water management and the development of sustainable conservation policies to maintain the ecological balance of Lake Bokuok